Pendampingan Kewirausahaan dan penyusunan Profil Bisnis Bagi UMKM Desa Krangkuten Kecamatan Gondang Kabupaten Mojokerto - Agus Sunaryo; Dwi Dewianawati; Mohamad Johan Efendi; Mokhammad Ridha; Mega Darmi Novita; Elly Joenarni; Dadang Purwo Ariwidodo (Lembaga Pengembangan Kinerja Dosen, 2026)
. Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting community economic growth. However, many MSME actors still face challenges in building business identity, developing marketing strategies, and managing finances effectively. Therefore, this community service program aimed to enhance the capacity of MSME actors through entrepreneurship mentoring and business profile development. The activity was conducted on December 8, 2025, at the Karangkuten Village Hall, Gondang District, Mojokerto Regency, involving 25 MSME participants. The methods used included counseling, training, discussions, and mentoring. The materials covered personal branding, marketing management, and business financial management. In addition to delivering the training materials, the service team also assisted participants in preparing business profiles as promotional tools and business identity enhancement. The results indicated that participants gained a better understanding of the importance of personal branding, marketing strategies, and financial management in supporting business development. The outputs of the program included business profiles and digital marketing profiles that can be utilized by MSMEs to expand market reach and improve business professionalism. This activity is expected to encourage MSME digital transformation and enhance business competitiveness and sustainability in Karangkuten Village.